Effect of Dietary Antarctic Krill Meal on Growth Performance, Muscle Proximate Composition, and Antioxidative Capacity of Juvenile Spotted Halibut, Verasper variegatus. Issue 4 (6th September 2017) - Yan, Junli; Chang, Qing; Chen, Siqing; Wang, Zhenjie; Lu, Bin; Liu, Changlin; Hu, Jiangcheng
Abstract: A 7‐wk feeding trial was conducted to evaluate the effects of dietary Antarctic krill meal (AKM) on the growth performance, proximate composition of muscles, and antioxidative capacity of juvenile spotted halibut. Six diets were formulated to contain about 50% protein and 8% lipid. A control diet (R0) without AKM and the other five diets with 8.1, 16.2, 24.3, 32.4, and 42.5% AKM supplementation (R10–50) to replace 10, 20, 30, 40, and 50% fishmeal protein were used to feed to juvenile spotted halibut. The juveniles were fed with each diet using three replicates and cultivated in the indoor culture system. Results showed that the specific growth rate, feed intake, and protein efficiency ratio in the R30 and R40 groups were significantly higher than that in other groups ( P  < 0.05). Survival rate in the R50 group was significantly lower compared with the R0 group and the other four AKM supplementation groups. Moreover, the rising AKM levels in diets had significant effects on the chemical composition of juvenile spotted halibut, showing significantly decreased contents of crude protein, but increased lipid and ash contents ( P  < 0.05). The total superoxide dismutase activity and catalase activity of serum and liver in AKM groups were significantly higher than those in the control group ( P  < 0.05). In contrast, the contents of malondialdehyde in serum and liver were significantly lower compared with the control group. These findings illustrate that a moderate AKM level in diets can significantly improve the growth performance, feed utilization, and antioxidative capacity in juvenile spotted halibut, which support the finding that AKM may be used as a good protein source for halibut in the aquafeed industry.